Harmoni Pendidikan Islam Moderat: Telaah Ayat-Ayat Moderasi dalam Tafsir Al Azhar Karya Buya Hamka Melalui Pendekatan Tafsir Tematik - Shohib, Muhammad (Universitas Batanghari Jambi, 2024)
This research aims to interpret the verses on moderation and moderate Islamic education according to Buya Hamka in Tafsir Al-Azhar. This research method uses a library approach and qualitative research type. Through a thematic interpretation approach. The results found about the concepts emphasized by Buya Hamka in his interpretation of moderate verses in the Al-Quran. These concepts include the right to freedom in all aspects of life, including freedom of belief, as well as rationalism in seeking the truth, as expressed in QS Al-Baqarah verse 256. Understanding of piety, social spirit regardless of racial, ethnic or religious differences, and Polite behavior towards neighbors, even non-Muslims, as explained in QS Al-Mumlahanah verse 8, is the main basis in the concept of moderate Islamic education. Apart from that, the concept of moderation verses also teaches the values of getting to know each other, interacting, helping each other, and cross-religious cooperation to advance civilization, in accordance with QS Al-Hujurot verse 13. The concept of having a moderate spirit and prohibiting extremism, as found in QS An-Nisa' verse 171, becomes the basis for forming a balanced character of Muslims.